Osteofluorosis in free ranging California sea lions (Zalophus californianus) - Martinez, Margaret E.; Rivard, Michelle; Sykes, Chelsea; Isbell, Jaclyn; Grimes, Sarah W.; Poppenga, Robert; Duignan, Pádraig J. (Frontiers in Marine Science, 2023)
We report the first case series of osteofluorosis in free ranging marine mammals and documentation of baseline bone fluoride concentrations in this population; however, the exact source is not known. A stranded subadult male California sea lion, one subadult male carcass, and one partial carcass, presumably adult male, demonstrated osseous (bony) proliferations on various appendicular and axial bones. The most severe lesions were from the index case with symmetrical segmental circumferential periosteal new bone proliferation on the diaphysis of both femurs and humeri. This case, and the second case, also had significant segmental periosteal new bone proliferation on the mandibles as well as increased tooth wear with dull enamel. Total fluoride concentrations in various bones of the cases ranged from 3,700 to 9,700 ppm dw, with a mean of 5,431 ppm dw, approximately twice the concentration in adult cattle with osteofluorosis. Ribs from four control California sea lions of various ages and both sexes had an average total fluoride of 1,575 ppm dw, which is three times as high as the bone fluoride concentration of normal adult cattle, but four times lower than the mean rib fluoride concentrations in the cases. This is the first report of osteofluorosis in free ranging marine mammals and documentation of baseline bone fluoride concentrations in this population. The exact source of the excessive fluoride levels is not known as male California sea lions have a large range and varied diet.